POLITIK HUKUM DALAM KEBIJAKAN PENANGANAN KRISIS KEPERCAYAAN PUBLIK TERHADAP INSTITUSI PEMERINTAH DI ERA DIGITAL - Naek Efendi; Mustofa Kamil; Supendi; Tugimin Harjotaruno; Asep Mulyana; Muhammad Ruhunussa (CV. Lafadz Jaya, 2026)
The digital age has brought about a fundamental transformation in the dynamics of the relationship between government and society. On the one hand, digital technology provides broader access to information and greater government transparency; on the other hand, the digital age has also become a medium for the dissemination of information that can undermine public trust in government institutions. The crisis of public trust is a multidimensional phenomenon involving political, legal and social aspects. This study aims to analyse legal policy in the context of addressing the crisis of public trust in government institutions in the digital age, using a normative-empirical legal research method. The findings indicate that legal policy in this context must strike a balance between protecting the reputation of government institutions and upholding the right to freedom of expression and the right to public information. Effective legal policy must be progressive, participatory, and evidence-based. This study recommends a holistic approach that integrates regulatory, educational, and technological aspects in addressing the crisis of public trust.